Training Human Resources for Health in Selected States of Southern Nigeria - , E. U. Nwonwu; , E. A. Nwobi; , I. Obi; , N. C. Eze; , P. O. Okpako (Archives of Current Research International, 2018)
Human resources are the heartbeat of health service delivery. The health workforce determines health outputs and outcomes, drives health system performance etcetera. Shortages of health workforce are widespread and supply of healthcare professionals and other service providers are inadequate to meet requirements. The study was carried out to ascertain the number of students (Resident Doctors (Public health), Community Health Officers (CHO), Community Health Extension Workers (CHEW), Junior Community Health Extension Workers (JCHEW) that graduated by year and gender from the training institutions within the period under review. This was a retrospective study that involved a five year review of some training health institutions in Southern (Enugu, Ebonyi, Cross River States) Nigeria. Data were extracted from the institution’s records. More males than females (3:1) graduated from the training facilities for Resident Doctors, while more females than males (3:1) graduated from the training facilities for CHOs, CHEWs and JCHEWs within the period of study. There is need for training of more human resources for health, so that the required health workforce would be met in the reviewed states.